Analisis Proses Kapabilitas Iodine Value (IV) Crude Palm Kernel Oil Stearin (CPKST) di Pabrik Kelapa Sawit - yola, Melfa; Al-As'ad, Faiz; Lubis, Fitriani Surayya; Nofirza, Nofirza; Wahab, Mohammad Ikbar Bin Abdul (SURYA TEKNIKA, 2023)
PT. XYZ, is a company engaged in the processing of palm kernel (CPKO). CPKO was separated into CPKOL (crude palm kernel olein) and CPKST (crude palm kernel stearin). There is a discrepancy in the quality standard of IV quality (Iodine Value) at CPKST which affects the selling price and consumer demand. Determination of the value of IV by the company ranges from 5-7. Grouping and data collection of IV values was carried out for 3 months, then the data was analyzed using statistical quality control (SQC) methods of I-MR control charts, process capabilities, and cause-and-effect diagrams. This study aims to analyze the process capability of IV CPKST which is not in accordance with company standards. The results of data processing show that some CPKST IV values are outside the control limits, moving ranges with UCL 0.70 and LCL 0, individuals with UCL 7.33 and LCL 6.18, and process capability is said to be good with a value range of 6.37 and 1 A causal analysis was performed using a fishbone diagram. Based on the results of the fishbone diagram analysis, the factors of quality non-compliance are found in humans, machines and methods. It is necessary to make efforts to maintain and maintain product quality based on existing regulations.